A Review of Pretreatment Methods to Improve Agri-Food Waste Bioconversion by Black Soldier Fly Larvae - Peguero, Daniela A.; Gold, Moritz; Vandeweyer, Dries; Zurbrügg, Christian; Mathys, Alexander (Frontiers in Sustainable Food Systems, 2022)
As the world population increases, food demand and agricultural activity will also increase. However, approximately 30 – 40% of the food produced today is lost or wasted along the production chain. Increasing food demands would only intensify the existing challenges associated with agri-food waste management. An innovative approach to recover the resources lost along the production chain and convert them into value-added product(s) would be beneficial. An alternative solution is the use of the larvae of the black soldier fly (BSFL), Hermetia illucens L., which can grow and convert a wide range of organic waste materials into insect biomass with use as animal feed, fertilizer and/or bioenergy. However, the main concern when creating an economically viable business is the variability in BSFL bioconversion and processing due to the variability of the substrate. Many factors, such as the nutritional composition of the substrate heavily impact BSFL development. Another concern is that substrates with high lignin and cellulose contents have demonstrated poor digestibility by BSFL. Studies suggest that pretreatment methods may improve the digestibility and biodegradability of the substrate by BSFL. However, a systematic review of existing pretreatment methods that could be used for enhancing the bioconversion of these wastes by BSFL is lacking. This paper provides a state-of-the-art review on the potential pretreatment methods that may improve the digestibility of substrates by BSFL and consequently the production of BSFL. These processes include but are not limited to, physical (e.g., mechanical and thermal), chemical (alkaline treatments), and biological (bacterial and fungal) treatments.